Metal-organic framework materials for low-k dielectrics and selective sensing applications - Babal, AS (2021)
Metal-organic frameworks (MOF) are fascinating hybrid materials, gained widespread attention from the scientific community since their emergence about three decades ago. The high porosity and tailorability of MOF structures make them an ideal candidate material for both low-k dielectrics and electrical sensing applications. In this work, an in-depth study on different MOFs was carried out to explore the influence of host-guest interaction and external stimuli including pelleting stress, operating temperature, and frequency, on MOF dielectrics. Additionally, a mechanism was proposed to identify the exceptional MOF materials for target guided electrical sensing and optimise the sensor preparation parameters to enhance its selectivity and sensitivity to revolutionise the conventional electrical sensors. Both polycrystalline (in the form of pellets) and single-crystal MOF samples were studied to gain a deeper insight into both areas.